Identifikasi Telur Cacing Tambang Ancylostoma duodenale Terhadap Pekerja Pengangkut Sampah Di Dinas Lingkungan Hidup Rantau Prapat Kabupaten Labuhan Batu - Sri Muri dasa Wardhani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The prevalence of helminthiasis in Indonesia is still high, between 60% - 90%, especially in rural areas and slums suffer from stomach worm infection depending on location and environmental sanitation. Hookworm is a worm that is quite dangerous. The disease caused by hookworms, namely Ancylostomiasis, can cause anemia in sufferers. Worm infections occur in people who often do not use Personal Protective Equipment (PPE) when working in trash bins and are accompanied by poor personal hygiene. This research is experimental in nature by conducting laboratory tests on the feces of garbage collection workers at the Rantau Prapat Environmental Service, Labuhan Batu Regency, which was carried out from 22 November 2021-22 December 2021 with a sample of 30 samples. The results showed that of the 30 people examined, 17 people (56.67%) were infected with hookworm eggs and 13 people (43.33%) were not infected with hookworm eggs. Based on the educational background of the workers, 3 people with high school education and all three were negative (0%), junior high school education 15 people who were examined 8 people (53.31%) were positively infected and 7 people (46.69) were not infected, elementary education 8 people who were examined 6 people (75%) were positively infected and 2 people (25%) were not infected. Not attending school 4 people were examined 3 people (75%) were positive for infection and 1 person (25%) was not infected.